Pengaruh Jumlah Produksi, Biaya Produksi dan Etos Kerja Islam Terhadap Pendapatan Petani Karet di Desa Wanareja Kecamatan Rimbo Ulu - Novi Nurhayati; Elyanti Rosmanidar; Fauzan Ramli (Komunitas Dosen Indonesia, 2024)
The aim of conducting this research is to measure the magnitude of the impact on total production, production costs and Islamic work ethic on income. The total population inthis study was 608 respondents with a sample size of 86 farmers measure using the slovin formula, to obtain samples that are appropriate to research using purposive sampling techniques. The type of research that researchers use is quantitative research. This research uses multiple linear regression analysis with the IMB SPAA version 26 tool. The results of the t test obtained significant values for the amount of production (X1) namely 0,000 < 0,05, production costs (X2) namely 0,000 < 0,05, and Islamic wor ethic (X3) namely 0,00 < 0,05, this means that it has a partial effect on income. In the results of the f test the undependent variables ( total production, production costs and Islamic work ethic) together have a significant effect on income (Y). the results of the coefficient of determination test are 0,756 or 75,6%, then it can be interpreted that variables of total production, production costs and Islamic wor ethic is able to interpret the income by 75,6%, while around 24,4% is explained by factors beyound the scope of this study